1972
DOI: 10.1113/expphysiol.1972.sp002152
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Hepatic Microvessels

Abstract: The response of microvessels of the intact liver to various stimuli was observed in the anaesthetized rat by a modified transillumination tbchnique, permitting photomicrography at any time during the direct microscopic Rbservation. Adrenaline The hepatic circulation has been studied by many methods but the results were often controversial [Grayson and Mendel, 1965]. Therefore, it seemed worthwhile to examine further the responses of hepatic microvessels to various stimuli. This paper reports the results of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
1984
1984

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This may indicate functional differences between the vasculature in intact and isolated liver. In transillumination studies on rat livers noradrenaline and adrenaline caused sinusoidal constriction (Seneviratne 1950, Ho 1972) and redistribution of the intrahepatic blood flow (Wakim 1944). This was to some extent confirmed in a radioangiographic study in cats (Daniel and Prichard 1951 ) .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This may indicate functional differences between the vasculature in intact and isolated liver. In transillumination studies on rat livers noradrenaline and adrenaline caused sinusoidal constriction (Seneviratne 1950, Ho 1972) and redistribution of the intrahepatic blood flow (Wakim 1944). This was to some extent confirmed in a radioangiographic study in cats (Daniel and Prichard 1951 ) .…”
Section: Discussionmentioning
confidence: 74%
“…Transillumination studies have revealed that catecholamines may change the intrahepatic distribution of blood flow, causing a decrease in the number of perfused sinusoids (Wakim 1944, Seneviratne 1950, McCuskey 1966, Ho 1972. Th' is concept has to some extent been supported by Daniel and Prichard (1951) in a radioangiographic study.…”
mentioning
confidence: 97%